Satellite communications and navigation systems - Del Re, Enrico; Ruggieri, M. (Signals and communication technology, 2008)
Satellite Communications and Navigation Systems publishes the proceedings of the 2006 Tyrrhenian International Workshop on Digital Communications. The book focuses on the integration of communication and navigation systems in satellites.